2019
DOI: 10.31235/osf.io/8j9zv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplatform MOOC Analytics: Comparing Global and Regional Patterns in edX and Edraak

Abstract: While global massive open online course (MOOC) providers such as edX, Coursera, and FutureLearn have garnered the bulk of attention from researchers and the popular press, MOOCs are also provisioned by a series of regional providers, who are often using the Open edX platform. We leverage the data infrastructure shared by the main edX instance and one regional Open edX provider, Edraak in Jordan, to compare the experience of learners from Arab countries on both platforms. Comparing learners from Arab countries … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…A kooperáció egyik megnyilvánulási formája az egyre elfogadottabbá váló mikrokreditrendszer. 30 A mikrokreditrendszer lényege, hogy a hallgatók a diplomához szükséges tudást és krediteket részenként gyűjtik össze, és a rendszerhez kapcsolódó egyetemek elfogadják egymás megfelelő témában nyújtott kreditjeit. Az Európai Felsőoktatási Térség kreditátviteli rendszere jól be tudná fogadni ezt az újfajta együttműködést, ennek ellenére magyar kezdeményezésről mindezidáig csak a Kárpát-medence vonatkozásában, és az óbudai Egyetem részéről, kizárólag magyar nyelvű kurzusokra vonatkozóan hallottunk.…”
Section: Táblázat • a 2021 Februárjában Működő Mooc-platformok Listája (Forrásunclassified
“…A kooperáció egyik megnyilvánulási formája az egyre elfogadottabbá váló mikrokreditrendszer. 30 A mikrokreditrendszer lényege, hogy a hallgatók a diplomához szükséges tudást és krediteket részenként gyűjtik össze, és a rendszerhez kapcsolódó egyetemek elfogadják egymás megfelelő témában nyújtott kreditjeit. Az Európai Felsőoktatási Térség kreditátviteli rendszere jól be tudná fogadni ezt az újfajta együttműködést, ennek ellenére magyar kezdeményezésről mindezidáig csak a Kárpát-medence vonatkozásában, és az óbudai Egyetem részéről, kizárólag magyar nyelvű kurzusokra vonatkozóan hallottunk.…”
Section: Táblázat • a 2021 Februárjában Működő Mooc-platformok Listája (Forrásunclassified
“…While trends and demographics of students in virtual learning environments (VLE) and MOOCs have been studied (e.g. (Ruipérez-Valiente et al, 2019)), Meaney and Fikes (Meaney and Fikes, 2019) have recently proposed that the feedback-loops of the innovations, as well as the research in LA are influenced by the bias of the early adopters. Specifically, they have found that the participants of MOOCs are often well-educated and less in need of learning interventions (Meaney and Fikes, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies that have discussed the impact of language and culture in learning [8], and previous researchers have linked the country of origin of MOOC participants to different behavioral patterns in the course [10] or to social identity threat in less developed countries [9]. Previous work that compared Arab learners in both Edraak (an Arabic MOOC provider) and edX found that learner populations in Edraak had a wider range of education levels and a more even gender, and the courses showed more favorable completion trends [12]. This previous work suggested that regional MOOC providers might be better positioned to fulfil their learners' needs as they offer courses in their local language, and taught by instructors of similar culture and background.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we describe the methodology "Multiplatform MOOC Analytics" that we have applied to put together data and analysis of more than ten MOOC providers. While a simplified version of this method was previously proposed [12], it is the first time that we apply it with a large number of providers and institutions. We also provide preliminary results on how a number of demographic variables are distributed across all of these platforms.…”
Section: Introductionmentioning
confidence: 99%